AI's Role in Collaborative Learning Settings in Higher Education – A Systematic Review - Pernu, Henna; Paananen, Sanna; Aksovaara, Satu; Silvennoinen , Minna (38th Bled eConference: Empowering Transformation: Shaping Digital Futures for All: Conference Proceedings, 2025)
There is increasing demand for teamwork and collaboration proficiencies, which require recalibration of workforce capabilities. As artificial intelligence reshapes societal and professional demands, higher education must adapt by equipping students with essential skills for evolving workplace needs. This systematic review aims to map the perspectives explored and the observed effects of using AI in collaborative learning among higher education students. The reviewed 34 studies primarily explored how AI enhances collaborative learning, targeting group performance, collaboration, knowledge building, and social interactions. Findings showed that integrating AI into collaborative learning situations can promote both collaborative and individual learning in various higher education contexts. This review provides an overview of AI's role in collaborative learning settings, highlights current development, and identifies gaps for further research. It also serves as a source for educators, policymakers, and researchers interested in leveraging AI to foster enriching educational experiences.